Cross the water blues : African American music in Europe - Wynn, Neil A. (American made music series., 2007)
This unique collection of essays examines the flow of African American music and musicians across the Atlantic to Europe from the time of slavery to the twentieth century. In a sweeping examination of different musical forms--spirituals, blues, jazz, skiffle, and orchestral music--the contributors consider the reception and influence of black music on a number of different European audiences, particularly in Britain, but also France, Germany, and the Netherlands. The essayists approach the subject through diverse historical, musicological, and philosophical perspectives. A number of essays doc.